Perancangan Ruang Apresiasi dan Edukasi Bagi Komunitas Seni Pertunjukan di Surabaya - Tencilia Asen Agatha (Intra, 2017)
Performing arts is one of art that people want to know include Surabaya citizen. Several communities performing arts in Surabaya have formed that they fans performing arts which has had several branches, gather and exchange ideas without a lack of space. Interior design of performing arts aims to give facilities space that fans art particulary performing arts have a roof to appreciating and show their art on society. Either in exhibition, performances, and share the advantages and their knowledge people who wants to decide to join in the art community. The performance art building is not limited. Everyone can enjoy this facility from child to elderly. In fact all kinds of the culture can be appreciating on this place. But the main target performing arts building is the performing arts community.The concept of design performing arts is appreciative and educative, which distributed through work. Educative is educating and teaching. In accordance with the user, and provide characteristic the artist who likes nature.